A comparative adsorption study of aflatoxin B1 and aflatoxin G1 in almond butter fermented by Lactobacillus fermentum and Lactobacillus delbrueckii subsp. lactis. (June 2020) - Hashemi, Seyed Mohammad Bagher; Amiri, Mohammad Javad
Abstract: Due to worldwide problems of mycotoxins such as Aflatoxin B1 (AFB1 ) and aflatoxin G1 (AFG1 ) in feeds, there is a lot of attention for low costs, practical and high efficiency detoxification methods. The goal of the present study was to examine the capability of two bacteria including L. delbrueckii subsp. lactis and L. fermentum for detoxification of AFB1 and AFG1 in almond butter at 35, 37 and 39 ο C during 32 h of fermentation with analyzing kinetic, equilibrium and thermodynamic adsorption data. The adsorption isotherm was ideally fitted to Langmuir–Freundlich model and kinetic data followed pseudo-first-order model. The results implied that the maximum adsorption capacity by both bacteria for AFB1 and AFG1 was in the order of L. delbrueckii subsp. lactis - AFG1 (0.577 μg kg −1 ) > L. fermentum - AFG1 (0.398 μg kg −1 ) > L. delbrueckii subsp. lactis - AFB1 (0.357 μg kg −1 ) > L. fermentum - AFB1 (0.315 μg kg −1 ). According to the thermodynamics parameters, the adsorption of AFB1 and AFG1 by both bacteria was spontaneous, endothermic and physical in nature. The results support the conclusion that L. delbrueckii subsp. lactis could be used as a practical and effective method for the detoxification of AFB1 and AFG1 in almond butter. Highlights: Efficient adsorption of AFB1 and AFG1 by L. delbrueckii subsp. lactis and L. fermentum . Adsorption of AFB1 and AFG1 is described by Langmuir–Freundlich model. Pseudo-first-order model was the superior kinetic model. The adsorption of AFB1 and AFG1 is spontaneous, endothermic and physical in nature. L. delbrueckii subsp . lactis was more efficient than L. fermentum .